Divinity and Motifs on Early Indian Coins - Banerji, Arundhati (Ancient Pakistan, 2021)
Coins as a symbol of ideas and ideals, working behind the mind of the rulers at different periods, open up a most comprehensive and interesting study. Although references to coins occur in the early Indian Literature, punch-marked coins are found the earliest ones spread over a large area from Pakistan in the northwest to Tamilnadu (India) in the south; from Taxila (Pakistan) in the west to Chandraketugarh (India) in the east. These comprise both silver and copper coins; in the first group, bent bar coins from Taxila are also included. Their chronology is not definite, however, their beginning may be assigned to the sixth-fifth century BC.